استثمار البحث العلمي لتحقيق التنمية المستدامة في المنظمات التعليمية دراسة تحليلية لآراء عينة من اساتذة الكليات الاهلية في محافظات الفرات الاوسط - ناصر عدنان مطر; احمد جنان شهاب (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research aims to review the investment of scientific research to achieve sustainable development, know its content and substance, clarify the developmental philosophy that forms the basis for it, and address the role of higher education organizations at the current stage in order to adopt solid scientific research strategies, in view of the pioneering role played by the university as one of the institutions. Knowledge that contributes to achieving sustainable development in the Iraqi environment with its reality and the challenges it faces. To apply this, reliance was placed on the descriptive analytical approach, which is based on deducing specific ideas from a general idea, with a realistic analysis that links diagnosis and treatments on the one hand and reality on the other hand from the point of view An analysis of the opinions of a sample (177) of faculty members in private colleges in the Republic of Iraq for the academic year 2023-2024. The study concluded that sustainable development is a way of life and a way of living governed by humane ethical frameworks, in addition to being a development pattern characterized by rationality and maturity that seeks to create a society with less tendency to To the materialistic tendency while changing many of the prevailing concepts that are based on the principle that more is better in various aspects of life, and these conclusions led to a set of recommendations, the most prominent of which was spreading the culture of scientific research in schools and educational institutions in the form of basic study materials or competitions and research participations dealing with Various issues in development.